Synthesis and antimicrobial evaluation of some 4- or 6-chloroisatin derivatives - Pandeya S.N.; Raja A.S.; Nath G. (My University, 2025)
Two series of chloroisatin-3-semicarbazones and hydrazones have been designed and prepared by condensing 4-chloro and 6-chloroisatin with several substituted semicarbazides and related bioisosteric hydrazides, respectively. Investigation of in vitro antimicrobial activity of compounds has been performed by agar double dilution method against nine pathogenic bacteria and four pathogenic fungi. The title compounds are also screened for their antitubercular activity against Mycobacterium tuberculosis H37 Rv using microplate alamar blue assay. Many of the synthesized compounds exhibit significant antibacterial activity in comparison to sulphamethoxazole, trimethoprim and some compounds show good antifungal activity comparable to clotrimazole. The semicarbazones arised from the 6-chloroisatin series have exhibited good antimicrobial activity than that obtained from 4-chloroisatins. Compounds, 6-chloroisatin-3-(2′-chlorophenyl) semicarbazones 1b and 6-chloroisatin-3-(4′-bromophenyl) semicarbazone 4b have shown a promising activity in both antibacterial and antifungal screenings. None of the compounds has been found to be active in antitubercular screening.